2013
DOI: 10.4321/s1130-01082013001000016
|View full text |Cite
|
Sign up to set email alerts
|

Zollinger-Ellison syndrome

Abstract: We have closely read the article entitled "Pancreatic endocrine tumours or apudomas" (1) published in your journal in April of 2011. Zollinger-Ellison syndrome (ZES) is a rare entity that is found amongst the differential diagnosis of pancreatic endocrine tumours. We present two clinical cases of ZES recently diagnosed in our centre. Case reportsCase report 1. This is a 50-year-old female with an 11-year history of epigastralgia and diarrhoea that only improved with proton pump inhibitors (PPIs) with a return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Gastric acid secretion is stimulated by various neuronal (vagal, enteric), paracrine (histamine) and hormonal (gastrin) factors, while somatostatin, glucagon-like peptide-1, cholecystokinin and atrial natriuretic peptide reduce secretory stomach activity [2]. Gastric hyperacidity states increase the risk of numerous gastrointestinal disorders and increase morbidity and mortality related to those pathologies [3][4][5]. Excessive secretion of gastric juice may cause destruction of the mucous protection barrier, the development of erosions, formation of ulcers ac---companied by inflammatory state [6,7] and, finally, the development of cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric acid secretion is stimulated by various neuronal (vagal, enteric), paracrine (histamine) and hormonal (gastrin) factors, while somatostatin, glucagon-like peptide-1, cholecystokinin and atrial natriuretic peptide reduce secretory stomach activity [2]. Gastric hyperacidity states increase the risk of numerous gastrointestinal disorders and increase morbidity and mortality related to those pathologies [3][4][5]. Excessive secretion of gastric juice may cause destruction of the mucous protection barrier, the development of erosions, formation of ulcers ac---companied by inflammatory state [6,7] and, finally, the development of cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal disorders, especially acid-related diseases, including peptic and duodenal ulcers, gastroesophageal reflux disease, upper GI bleeding, or stress-related mucosal disease, are currently serious health issues encountered very frequently in patients worldwide [ 1 ]. On the other hand, many gastrointestinal diseases, such as Zollinger-Ellison syndrome, retained antrum syndrome, antral G cell hyperplasia, and gastric outlet obstruction, are disorders whose etiology involves gastrin hypersecretion [ 2 4 ]. It has been shown that gastrin, histamine, and acetylcholine stimulate gastric acid secretion, while somatostatin, cholecystokinin, glucagon-like peptide-1, and atrial natriuretic peptide reduce secretory stomach activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that stress, unhealthy lifestyles, junk food, chemical food additives, Helicobacter pylori infection, and abuse of nonsteroidal anti-inflammatory drugs (NSAIDs) increase the risk of stomach diseases, such as erosions, ulceration of gastric mucosa, and/or gastric hyperacidity [ 20 ]. Moreover, disorders such as Zollinger-Ellison syndrome, antral G cell hyperplasia, and gastric outlet obstruction via gastrin hypersecretion cause long-term hyperacidity, leading to chronic ulceration of the gastric and duodenal mucosa [ 21 , 22 ]. Previous studies revealed that the prepyloric area of the stomach is a predictable place of occurrence of pathological changes, such as erosion, ulcers, and inflammatory condition in course of the gastric disorders [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%